2009
DOI: 10.3109/13697130903353478
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Japanese peri- and postmenopausal women

Abstract: Insomnia in Japanese peri- and postmenopausal women correlates more strongly with depressed mood than with vasomotor symptoms. Cessation of smoking may improve the women's sleep quality, and hormone therapy and nightly hypnotics are both effective treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 45 publications
6
57
0
Order By: Relevance
“…3,4 These vasomotor symptoms are considered at least partially responsible for sleep disorders after menopause. 5,6 Many women present with sleep disorders after menopause. 7 An epidemiological study conducted in São Paulo found that 81.6% of the interviewees had sleep complaints, and 52.1% of the respondents complained of insomnia.…”
mentioning
confidence: 99%
“…3,4 These vasomotor symptoms are considered at least partially responsible for sleep disorders after menopause. 5,6 Many women present with sleep disorders after menopause. 7 An epidemiological study conducted in São Paulo found that 81.6% of the interviewees had sleep complaints, and 52.1% of the respondents complained of insomnia.…”
mentioning
confidence: 99%
“…26 -32 Specifically, we retrospectively analyzed the first-visit records of 351 Japanese perimenopausal and postmenopausal women aged 40 years or older who had enrolled in the Systematic Health and Nutrition Education Program conducted at the menopause clinic of the Tokyo Medical and Dental University Hospital from November 2007 to December 2012. All middle-aged women who had enrolled in this program were referred to our clinic for treatment of their menopausal symptoms, and all participants provided an informed consent form.…”
Section: Methodsmentioning
confidence: 99%
“…The MHR-QOL, developed and validated in our clinic, [26][27][28][29][30][31][32]34 is a modification of the Women's Health Questionnaire 35,36 and contains 38 items scored on a four-point or binary scale covering four major domains of a woman's health during menopause (physical health, mental health, life satisfaction, and social involvement). The physical health domain consists of nine items that assess vasomotor, somatic, and urinary symptoms, including frequent urination.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the study population have been described previously [5][6][7]. Briefly, the SHNEP was conducted at the Menopause Clinic of the Tokyo Medical and Dental University Hospital, Tokyo, Japan, between March 22, 1995, andDecember 16, 2009.…”
Section: Methodsmentioning
confidence: 99%